Diseases of sheep (Blackwell, 2007)
This book maintain its original core structure and its international approach to the many diseases which affect sheep. Special attention is given to specific regional disease problems in the Middle East, Southern Africa, Australia, New Zealand, North America and South America. Any veterinary surgeon or agriculturalist who works with sheep will continue to find the information in this book the most authoritative and comprehensive available.